2023
DOI: 10.1155/2023/3459377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissolved Oxygen and Chemical Scarification on Andrographis paniculata Seed Germination in Macrobubble Conditions

Abstract: Andrographis paniculata is used in Thai traditional medicine. This plant contains a bitter compound called andrographolide, which is highly effective in the prevention of many diseases. It is an effective treatment for infectious diseases and has a prophylactic effect owing to its powerful immunity-boosting benefits. Recently, it has been widely used to treat COVID-19. However, commercial planting of A. paniculata is performed by seeding, which leads to seed germination problems. The seed germination is relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Sodium hypochlorite scarification is one such method that has proven highly efficient in breaking physical seed dormancy. Recent studies [51,52] have reported significant improvements in seed germination, notably in Andrographis paniculata and Vanilla planifolia, following NaHClO 3 scarifications. In some cases, this scarification is combined with ethanol pre-treatment, with ethanol concentrations ranging from 50 to 96% [53,54], further enhancing the dormancy breakage process.…”
Section: Effect Of Seed Scarificationmentioning
confidence: 99%
“…Sodium hypochlorite scarification is one such method that has proven highly efficient in breaking physical seed dormancy. Recent studies [51,52] have reported significant improvements in seed germination, notably in Andrographis paniculata and Vanilla planifolia, following NaHClO 3 scarifications. In some cases, this scarification is combined with ethanol pre-treatment, with ethanol concentrations ranging from 50 to 96% [53,54], further enhancing the dormancy breakage process.…”
Section: Effect Of Seed Scarificationmentioning
confidence: 99%